The Mesoproterozoic ‘seismite’ at Laiyuan (Hebei Province, E China) re-interpreted - Loon, A.J. (Tom) Van (Geologos, 2014)
A 1-million m3 breccia near Laiyuan (Hebei Province, E China) occurs as a block-like lithological unit between dolo-stones of the 1.55-1.45 Ga (Early Mesoproterozoic) Wumishan Formation. It has previously been interpreted as a seismite, but it appears not to fulfil any of the commonly accepted criteria that jointly are considered diagnostic for seis-mites. Its presence in a graben-like structure with almost vertical bounding fault planes rather indicates an origin as a (submarine) valley fill. As the valley originated by tectonic activity in the form of faulting, the breccia can be considered as a secondary effect of seismic activity, but it does not represent a seismite.